Family Power and Corporate Investment Efficiency - Alhadi, A.; Eulaiwi, Baban; Taylor, G. (2018)
This paper examines the relationship between family power and investment efficiency of the GCC firms. We develop a new model of family power involvement on the board of directors and executive level to capture the effect of family power on investment efficiency. We find family power reduces both under and over-investment of the GCC firms. We find this reduction significant due to ability of the family power to reduce both agency costs and information asymmetry. However, we find this power is alleviated when firms are in mature stage. Our results robust using several measures of family involvement, investment efficiency and endogeneity test.